Characterization of Zr-Al Substituted M-Type Barium Hexaferrite Synthesized by Co-Precipitation Method - Akhtar Shahia, Humaira; Shifa, Muhammad Shahzad; Mehboob, Zeshan; Muhammad Hashim; ur Raheem, Faseeh (Journal of Materials and Physical Sciences, 2021)
Structural properties of Zr-Al substituted M-type of barium hexaferrites, having compositions Ba1-xZr0.5xAl0.3Fe11.7O19, (x= 0.0, 0.1, 0.2, 0.3, 0.4, 0.5) are studied, which were synthesized by using co-precipitation method. These prepared samples are characterized by X-RAY diffraction (XRD) to confirm hexaferrites structure. Fourier transform infrared spectroscopy is used to make tetrahedral (higher frequency band) and octahedral (lower frequency band) clusters of metal oxides in hexaferrites and confirmed the formation of hexaferrites structure. (FESEM) Field emission scanning electron microscopy was used to give micrographs to show that grains are platelet like shaped, which agrees very well with hexaferrites structure. The particle morphology is observed to be porous and non-uniform. The grain size is decreased initially, and then increased with Zirconium additions. Scherer’s formula is applied to calculate particle size, which is observed to change in the range of 18.86 nm-9.43 nm. The grains are bounded together due to interfacial surface tension forces. The optical properties are also studied by UV Vis spectrometer to find the energy band gap, in the range of 2.09ev - 5.15ev and absorbance peak having the range 237.9nm - 252.13nm. This change in energy band gap and absorbance peak is due to the change in the grain size on the zirconium substitution.